FAKTOR-FAKTOR PENDORONG MINAT WIRAUSAHA STARTUP - Indarto Indarto; Chatarina Yekti Prawihatmi (Universitas Semarang, 2021)
The number of startup businesses in Indonesia has increased rapidly from 2013 to the present. Some succeed, but more fail in the middle of the road. The high potential for failure does not make interest in startup entrepreneurship decrease, but quite the opposite. This study examines what factors drive theinterest of entrepreneurs in the startup business. The interest in entrepreneurship is influenced by many factors, both internal and external factors, including; income expectations, family environment, education and others. The study population was startup entrepreneurs in the city of Semarang. The research sample is in accordance with the statistical feasibility of 30 startup entrepreneurs with the Snowball method. The data analysis technique used is factor analysis. The results of the analysis showed that various factors that boosted entrepreneurial interest in startups were grouped on 5 factors, namely: the availability of facilities and opportunities, opportunity factors, self-actualization factors, self-ability factors and community recognition factors.Jumlah usaha startup di Indonesia meningkat pesat mulai tahun 2013 sampai saat ini. Beberapa berhasil , tetapi lebih banyak yang gagal di tengah jalan. Potensi kegagalan usaha startup ternyata cukup tinggi . Tingginya potensi kegagalan tersebut tidak membuat minat untuk berwirausaha startup menurun, namun justru sebaliknya. Penelitian ini mengkaji factor apa saja yang mendorong minat wirausahawan dalam bisnis startup. Minat berwirausaha dipengaruhi banyak faktor baik faktor internal dan faktor eksternal, antara lain; ekspektasi pendapatan, lingkungan keluarga, pendidikan dan lain-lain. Populasi penelitian ini adalah wirausahawan startup di Kota Semarang. Sampel penelitian sesuai dengan kelayakan statistic yaitu sebanyak 30 wirausahawan startup dengan metode Snowball. Teknik analisis data yang digunakan adalah analisis faktor. Hasil Analisis menunjukkan bahwa berbagai faktor yang mendorong minat wirausaha startup mengelompok pada 5 faktor yaitu: Faktor tersedianya fasilitas dan kesempatan, faktor peluang, faktor aktualisasi diri, faktor kemampuan diri dan faktor pengakuan dari masyarakat.